Cup filler - Yaser Kharouf; Hamzah Fattouh (My University, 2024)
As more emphasis is being put to automating the production lines, The cub filling project is considered one of the most important methods of innovation in the use of production and filling lines compared to other methods and mechanisms that waste time and effort, as this technology works to save time, increase productivity and reduce energy use ,The project focuses on a system for filling cups of different sizes and flavors, using technology whereas height measurement using LDR module to determine the size of the cup whether large or small. Depending on the attributes detected the system has dispensing systems such as solenoid valves or some pumps which dispense the appropriate substance in to the cup. On board the system is the microprocessor and microcontroller (Arduino) that interfaces with the sensors to control them and carry out data analysis and even control output devices (actuators). The project also fields a conveyor belt that is purposed with distributing cups during [among] certain levels of detection and filling. The main purpose of this project is to enhance production output with the poorly done task of filling the recognized cup with some product while reducing the human effort and parameters set for the dispensing system are dispensed automatically.